Climate Security Observatory - Somalia - Sax, Niklas; Schapendonk, Frans; Kenduiywo, Benson; Villa, Victor; Craparo, Alessandro; Benzid, Rym; Nunow, Abdimajid; Pacillo, Grazia (2024)
Climate security explores whether climate change increases the risk of armed conflict and, if so, under which circumstances this relationship occurs. People in fragile and conflict-affected areas are also among the most vulnerable to climate change, making it vital to understand the climate-conflict interplay for resilience and peacebuilding. A major challenge for governments in vulnerable, fragile, and conflict-affected regions is managing these complex interactions. Currently, they lack effective tools to implement climate strategies that address social grievances driving conflict and adapt to changing dynamics. In response, conflict-sensitive approaches to climate action are gaining support as mechanisms to ensure transitions to carbon-neutral economies and climate-resilient societies are equitable and aligned with peacebuilding goals. This report summarizes six intersecting pathways between climate, peace, and security in Somalia developed through a multi-methods approach. It also assesses Somalia's current policy landscape to evaluate whether it currently evidences strategic and operational linkages across key policy sectors for climate, peace, and security, and puts forward a set of policy and programming recommendations to orient climate action to mitigate underlying drivers of conflict and contribute to a sustainable peace.